The low lying scalar resonances in the D0 decays into Ks0 and f0(500), f0(980), a0(980) - Ju-Jun Xie; Lian-Rong Dai; Eulogio Oset (Physics Letters B, 2015)
The D0 decay into Ks0 and a scalar resonance, f0(500), f0(980), a0(980), are studied obtaining the scalar resonances from final state interaction of a pair of mesons produced in a first step in the D0 decay into Ks0 and the pair of pseudoscalar mesons. This weak decay is very appropriate for this kind of study because it allows to produce the three resonances in the same decay in a process that is Cabibbo-allowed, hence the rates obtained are large compared to those of B¯0 decays into J/ψ and a scalar meson that have at least one Cabibbo-suppressed vertex. Concretely the a0(980) production is Cabibbo-allowed here, while it cannot be seen in the B¯s0 decay into J/ψa0(980) and is doubly Cabibbo-suppressed in the B¯0 decay into J/ψa0(980) and has not been identified there. The fact that the three resonances can be seen in the same reaction, because there is no isospin conservation in the weak decays, offers a unique opportunity to test the ideas of the chiral unitary approach where these resonances are produced from the interaction of pairs of pseudoscalar mesons.